Getting Real about body image: A qualitative investigation of the usefulness of the Aerie Real campaign. (September 2019) - Rodgers, Rachel F.; Kruger, Lou; Lowy, Alice S.; Long, Stephanie; Richard, Chloe
Highlights: Perceptions of diverse advertisements without digital alterations were explored. The images were perceived positively, and judged to promote body diversity. Young women found the images to be helpful for body image. Brand values and models' support of the campaign were also positively judged. Abstract: This study qualitatively examined perceptions of the Aerie Real campaign that utilized images that had not been digitally modified, as well as its capacity to contribute to positive body image. A sample of 35 college women, of mean age of 19.48 (range = 18–23 years) participated in individual interviews focused on their perceptions and reactions to the images included in the Aerie Real campaign. They also described the impact of the campaign on their brand perceptions and consumer intentions, as well as their attitudes towards social policy targeting the use of digital airbrushing. Most participants reacted to the images positively and perceived them as representing body diversity across several dimensions. In addition, the majority of participants found the images to be helpful for promoting positive body image and acceptance, through both appearance comparisons, and the modeling of body confidence. In addition, many participants expressed being more likely to purchase products from Aerie and support for the brand. Overwhelmingly, participants called for widespread portrayals of diverse bodies in media, although only partial support emerged for achieving this through policy. These findings support the usefulness of increasing body diversity in media and limiting thin-ideal images as means of promoting positive body image.